Relationships among Special Education Teachers' Knowledge, Instructional Practice and Students' Performance in Reading Fluency. Issue 2 (7th February 2019) - Park, Yujeong; Kiely, Mary Theresa; Brownell, Mary T.; Benedict, Amber
Abstract: The purpose of this study was to explore the relationships among (1) special education teachers' knowledge for teaching reading fluency, (2) the specific instructional practices they used in fluency instruction, and (3) gains of students with specific learning disabilities (SLD) on a performance measure of oral reading fluency (ORF). Analyses based on multilevel linear modeling and analysis of covariance indicated that for 42 special education teachers teaching third, fourth, and fifth graders with SLD in intensive reading groups, teachers' knowledge for teaching reading fluency predicted student gains on ORF measures, but did not predict their instructional practice. Furthermore, teacher practice did not predict student gains on ORF. Practical implications and future research are discussed.